Efficacy and Safety of Berberine Alone for Several Metabolic Disorders: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Ye, Yu; Liu, Xiufen; Wu, Ninghua; Han, Yanqi; Wang, Jiawen; Yu, Yuandong; Chen, Qingjie (Frontiers in Pharmacology, 2021)
Background: Metabolic activity is the basic life activity of organisms and the fundamental for maintaining body functions. With the improvement of living standards, the incidence of metabolic disorder is also increasing. At present, most of the clinical treatment strategies and meta-analysis for metabolic disorder uncover that combined medicines with berberine ameliorate several metabolic disorders. However, evidence to disclose the therapeutic effect of berberine treatment alone and the possible factors affecting the efficacy is limited. Therefore, we have formulated strict inclusion criteria and selected more reliable data for meta-analysis through more refined screening strategies to provide evidence and guidance for clinical decision-making and understand the effect of berberine treatment alone and the factors affecting its efficacy. Methods and results: Using meta-analysis of “Cochrane Handbook for Systematic Reviews of Interventions” as guidelines, we searched PubMed, GeenMedical, Cochrane library, and china national knowledge infrastructure (CNKI) for trials reporting clinical treatment data of berberine. Another 417 trials were included through other sources to increase confidence in results. Among the 1,660 related documents retrieved from the four databases, 18 eligible documents were selected for analysis. Given the differences in trial design and measurement units, we used the standardized mean difference (SMD) method to eliminate the differences and then summarize the data for analysis. The main factors are triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), homeostasis model assessment-insulin resistance (HOMA-IR), and fasting plasma glucose (FPG). Random-effect model analysis was performed: TG (SMD: 0.94; 95%CI: 0.49,1.38; p = 0.00), TC (SMD: 1.06; 95%CI: 0.64, 1.48; p = 0.00), LDL (SMD: 1.77; 95%CI: 1.11,2.44; p = 0.00), HDL (SMD: −1.59; 95%CI: −2.32, −0.85; p = 0.00), HOMA-IR (SMD: 1.25; 95%CI: 0.25,2.24; p = 0.01), and FPG (SMD: 0.65; 95%CI: 0.28,1.03; p = 0.00). This study aimed to conduct a systematic review and meta-analysis of the literature to evaluate the therapeutic effect of berberine singly on metabolic diseases. Conclusion: Berberine can improve obesity and hyperlipidemia by reducing TG, TC, and LDL and increasing HDL; reduce insulin resistance to improve type Ⅱ diabetes; and prevent diabetic encephalopathy.